Social Media Marketing and Purchase Decisions - Frans Sudirjo; I Nyoman Tri Sutaguna; Andreas Tigor Oktaga; Chevy Herli Sumerli A.; Bunga Aditi (International Journal of Economics and Management Research, 2023)
The purpose of this study is to examine and analyze the effect of social media marketing on the number of visitors to Tekodeko Coffee in Semarang. Individuals that visited Tekodeko Coffee made up the research sample. This study used a sample size of 91 people drawn from original data collected via a questionnaire instrument. Validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, and hypothesis testing with multiple linear regression analysis, coefficient of determination testing, t-test, and f-test are all part of the data analysis method. According to the findings of our study, the factors Social Presence (X1) and Media Richness (X2) have no significant influence on the frequency of visits to Tekodeko coffee in Semarang.